Did the H1N1 Vaccine Reduce the Risk of Admission with Influenza and Pneumonia during the Pandemic? - Mahmud, Salaheddin M. (PLoS One, 2015)
BACKGROUND: The extent to which A(H1N1)pdm09 influenza vaccines prevented hospital admissions with pneumonia and influenza (P&I) during the 2009 pandemic remains poorly understood. We evaluated the effectiveness of the A(H1N1)pdm09 and seasonal influenza vaccines (TIV) used during the 2009 mass vaccination campaign in Manitoba (Canada) in preventing P&I hospitalization. METHODS: A population-based record-linkage nested case-control study. Cases (N = 1,812) were persons hospitalized with influenza (ICD-10:J09-J11) or pneumonia (ICD-10:J12-J18) during the study period. Age-, gender- and area of residence-matched controls (N = 7,915) were randomly sampled from Manitoba’s Population Registry. Information on receipt of A(H1N1)pdm09 vaccine and TIV was obtained from the Manitoba Immunization Monitoring System, a province-wide vaccine registry. RESULTS: Overall, the adjuvanted A(H1N1)pdm09 vaccine was 27% (95%CI 13–39%) effective against P&I hospitalization ≥ 14 days following administration. Effectiveness seemed lower among older (≥ 65 years) adults (10%; −16–30%), particularly when compared to under-5 children (58%; 30–75%). The number-needed-to-vaccinate to prevent 1 P&I admission was lowest among <4 year-olds (928) and ≥65 years (1,721). VE against hospitalization with laboratory-confirmed A(H1N1)pdm09 was 70% (39–85%) overall and (91%; 62–98%) ≥ 14 days following vaccination. DISCUSSION: Our data suggest that the adjuvanted A(H1N1)pdm09 vaccine was effective in preventing about 55–60% of P&I hospitalizations among children and younger adults who were at much higher risk of infection. Unfortunately, the vaccine was less effective among 65 or older adults. Despite that the vaccine still had a significant population-based impact especially among the very young (<5) and the older (≥ 65 years).